9‐Cyano‐10‐telluriumpyronin Derivatives as Red‐light‐activatable Raman Probes. Issue 2 (13th December 2022) - Kawatani, Minoru; Spratt, Spencer J.; Fujioka, Hiroyoshi; Shou, Jingwen; Misawa, Yoshihiro; Kojima, Ryosuke; Urano, Yasuteru; Ozeki, Yasuyuki; Kamiya, Mako
Abstract: Photoactivatable fluorescence probes can track the dynamics of specific cells or biomolecules with high spatiotemporal resolution, but their broad absorption and emission peaks limit the number of wavelength windows that can be employed simultaneously. In contrast, the narrower peak width of Raman signals offers more scope for simultaneous discrimination of multiple targets, and therefore a palette of photoactivatable Raman probes would enable more comprehensive investigation of biological phenomena. Herein we report 9‐cyano‐10‐telluriumpyronin (9CN‐TeP) derivatives as photoactivatable Raman probes whose stimulated Raman scattering (SRS) intensity is enhanced by photooxidation of the tellurium atom. Modification to increase the stability of the oxidation product led to a julolidine‐like derivative, 9CN‐diMeJTeP, which is photo‐oxidized at the tellurium atom by red light irradiation to afford a sufficiently stable oxidation product with strong electronic pre‐resonance, resulting in a bathochromic shift of the absorption spectrum and increased SRS intensity. Abstract : We developed 9CN‐TeP derivatives having a tellurium atom at the 10th position of xanthene as a reaction point of photooxidation. These red‐light‐activatable Raman probes show a bathochromic shift in the absorption spectrum and enhanced stimulated Raman scattering (SRS) intensity after red light irradiation.